Single Dose IV Peramivir is Safe and Effective in the Treatment of Pediatric Influenza. (4th October 2017) - Vanchiere, John; Plunkett, Stephanie; Annamalai, Rajasekaran; Julien, Katie; Peterson, James; Goisse, Marcy; Christensen, Shane; Mehta, Priyesh; Coleman, Stephen; Munoz, Flor; Flynt, Amy; Dobo, Sylvia; et al.
Abstract: Background: Peramivir (PVR) is a potent neuraminidase inhibitor with in vitro activity against all influenza virus subtypes. Previous studies demonstrated the efficacy and safety of PVR as a single dose intravenous (IV) treatment for acute uncomplicated influenza in adults. Methods: A phase 3 study compared age-appropriate doses of single dose IV PVR to 5 days of oral oseltamivir (OSE) (4:1 randomization, stratified by age) in pediatric subjects age 0 -17 years within 48 hours of onset of acute uncomplicated influenza. Plasma concentrations of PVR were measured up to 6 hours post dose. Serial viral titers were measured from nasopharyngeal swabs. Severity of influenza signs and symptoms were recorded in a diary. Results: 122 subjects were enrolled up to a data cutoff of March 31, 2017 (<2 yrs, n = 7; 2-<7yrs, n = 37; 7-<13 yrs, n = 48; 13–17 yrs, n = 30). Interim results are reported for the first 108 subjects randomized, of which 101 (94%) received study drug. Influenza was confirmed by PCR in 75 (74%) subjects who received study drug (Intent-to-treat-Infected [ITTI] population). Key endpoints are summarized: Conclusion: Treatment of influenza in pediatric subjects with single dose IV PVR or 5 days of oral OSE was generally safe and well tolerated. Whilst not powered for efficacy differences, trends were observed in more rapid reduction in virus shedding and symptom alleviation for PVR treated subjects compared with OSE. The study continues to enroll subjects < 7 years. Disclosures: J. Vanchiere, BioCryst Pharmaceuticals: Consultant and Investigator, Consulting fee and Research support; S. Plunkett, BioCryst Pharmaceuticals: Investigator, Research support; R. Annamalai, BioCryst Pharmaceuticals: Investigator, Research support; K. Julien, BioCryst Pharmaceuticals: Investigator, Research support; J. Peterson, BioCryst Pharmaceuticals: Investigator, Research support; M. Goisse, BioCryst Pharmaceuticals: Investigator, Research support; S. Christensen, BioCryst Pharmaceuticals: Investigator, Research support; P. Mehta, BioCryst Pharmaceuticals: Investigator, Research support; S. Coleman, BioCryst Pharmaceuticals: Investigator, Research support; F. Munoz, BioCryst Pharmaceuticals: Investigator, Research support; A. Flynt, BioCryst Pharmaceuticals: Consultant, Consulting fee; S. Dobo, BioCryst Pharmaceuticals: Employee,  Salary; E. Nagy, BioCryst Pharmaceuticals: Employee,  Salary; D. Kargl, BioCryst Pharmaceuticals: Consultant, Consulting fee; A. Mathis, BioCryst Pharmaceuticals: Employee,  Salary; P. Collis, BioCryst Pharmaceuticals: Employee,  Salary; W. Sheridan, BioCryst Pharmaceuticals: Employee, Salary